Referrals to a Phase I Clinic and Trial Enrollment in the Molecular Screening Era - Tan, Tira (Oncologist, 2019)
BACKGROUND. Enrichment of patients based on molecular biomarkers is increasingly used in early phase clinical trials. Molecular profiling of patients with advanced cancers can identify specific genomic alterations to inform decisions about investigational treatment(s). Our aim was to evaluate the outcomes of new patient referrals to a large academic solid tumor phase I clinical trial program after the implementation of molecular profiling. MATERIALS AND METHODS. Retrospective chart review of all new referrals to the Princess Margaret Cancer Centre (PM) phase I clinic from May 2012 to December 2014. Molecular profiling using either MALDI‐TOF hotspot mutation genotyping or targeted panel DNA sequencing was performed for patients at PM or community hospitals through the institutional IMPACT/COMPACT trials. RESULTS. A total of 971 new patient referrals were included for this analysis. Twenty‐seven percent of referrals assessed in clinic were subsequently enrolled in phase I trials. Of all new referrals, 41% had prior molecular profiling, of whom 11% (n = 42) were enrolled in genotype‐matched trials. Patients with prior molecular profiling were younger, more heavily pretreated, and had more favorable Princess Margaret Hospital Index (PMHI) scores. Eastern Cooperative Oncology Group (ECOG) performance status 0–1 (p = .002), internal referrals within PM (p = .002), and PMHI (p ≤ .001) were independently associated with successful trial enrollment in multivariable analysis. CONCLUSION. Although nearly half of new patients referred to a phase I clinic had prior molecular profiling, the proportion subsequently enrolled into clinical trials was low. Prior molecular profiling was not an independent predictor of clinical trial enrollment. IMPLICATIONS FOR PRACTICE. The landscape of oncology drug development is evolving alongside technological advancements. Recently, large academic medical centers have implemented clinical sequencing protocols to identify patients with actionable genomic alterations to enroll in therapeutic clinical trials. This study evaluates patient referral and enrollment patterns in a large academic phase I clinical trials program following the implementation of a molecular profiling program. Performance status and referral from a physician within the institution were associated with successful trial enrollment, whereas prior molecular profiling was not an independent predictor.